Flexible Stabilisation of the Degenerative Lumbar Spine Using PEEK Rods - Benezech, Jacques (Adv Orthop, 2016)
Posterior lumbar interbody fusion using cages, titanium rods, and pedicle screws is considered today as the gold standard of surgical treatment of lumbar degenerative disease and has produced satisfying long-term fusion rates. However this rigid material could change the physiological distribution of load at the instrumental and adjacent segments, a main cause of implant failure and adjacent segment disease, responsible for a high rate of further surgery in the following years. More recently, semirigid instrumentation systems using rods made of polyetheretherketone (PEEK) have been introduced. This clinical study of 21 patients focuses on the clinical and radiological outcomes of patients with lumbar degenerative disease treated with Initial VEOS PEEK(®)-Optima system (Innov'Spine, France) composed of rods made from PEEK-OPTIMA(®) polymer (Invibio Biomaterial Solutions, UK) without arthrodesis. With an average follow-up of 2 years and half, the chances of reoperation were significantly reduced (4.8%), quality of life was improved (ODI = 16%), and the adjacent disc was preserved in more than 70% of cases. Based on these results, combined with the biomechanical and clinical data already published, PEEK rods systems can be considered as a safe and effective alternative solution to rigid ones.